Pengalaman guru dalam mengajarkan pendidikan agama islam di era digital - Mita Lestari (Journal of Cross Knowledge, 2024)
This study explores the experiences of Islamic Education teachers in facing challenges and utilizing opportunities in the digital era. Using a qualitative case study approach, data was collected through in-depth interviews, participatory observations, and document analysis. The results reveal significant challenges, including diverse digital literacy levels among students, less interactive teaching methods, and evaluations focused on theoretical knowledge rather than practical application. The study proposes solutions such as innovative teaching methods, increased integration of digital tools, and a more comprehensive curriculum integrating online and offline activities. This research contributes to the development of more effective Islamic Education in the digital age, aiming to shape intellectually and morally strong students